2011
DOI: 10.4236/ns.2011.31010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solar eclipse on seawater

Abstract: Eclipse induced changes in solar radiation is a common interest of scientists all over the world. The disturbance of the heat balance along the supersonic travel of the trajectory of the Moon's shadow could generate gravity waves during solar eclipse, which results a reduction in the concentration of ozone layer in the stratosphere. We, in this context, conducted some experiments to detect the possible radiations reaching the surface of the earth and the impact of such radiation in seawater during the recent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The occultation of the solar disk arises due to the fact that the apparent diameters of the Sun and the Moon as viewed from the surface of the Earth are equal. The partial/total termination of the solar flux affects chemical reactions, production and transport of ionization in the ionosphere Galav et al, 2010;Kumar and Singh, 2012), boundary layer phenomena (Jayakrishnan et al, 2013), ozone production, loss and columnar concentration (Chakrabarty et al, 1997;Kumar and Rengaiyan, 2011) and many other related phenomena including the generation and propagation of gravity waves (Farges et al, 2003). Since an eclipse generally occurs at different times of the day in different seasons at different places (varied in latitudes and longitudes) on the globe, it provides unique opportunity to test the proposed hypothesis and to verify the earlier results.…”
Section: Introductionmentioning
confidence: 99%
“…The occultation of the solar disk arises due to the fact that the apparent diameters of the Sun and the Moon as viewed from the surface of the Earth are equal. The partial/total termination of the solar flux affects chemical reactions, production and transport of ionization in the ionosphere Galav et al, 2010;Kumar and Singh, 2012), boundary layer phenomena (Jayakrishnan et al, 2013), ozone production, loss and columnar concentration (Chakrabarty et al, 1997;Kumar and Rengaiyan, 2011) and many other related phenomena including the generation and propagation of gravity waves (Farges et al, 2003). Since an eclipse generally occurs at different times of the day in different seasons at different places (varied in latitudes and longitudes) on the globe, it provides unique opportunity to test the proposed hypothesis and to verify the earlier results.…”
Section: Introductionmentioning
confidence: 99%
“…Other astronomical phenomenon such as eclipses of the sun also affects the current state of the ocean. Kumar and Rengaiyan (2011) proved that the total solar eclipse that occurred on July 22, 2009…”
Section: The Effect Of Astronomical Phenomenon On Fauna and Maritime mentioning
confidence: 98%
“…Until now, there are studies that try to unite astronomy with ethnography, but they are only limited to the astronomical phenomenon and its impact on life. For example, Othman (2016) had studied the effect of a partial solar eclipse phenomenon on the behaviour of animals; Yonvitner, Aziz, Butet, and Pujiastuti (2009) had proved that fishermen catch less fish during a full moon; Kumar and Rengaiyan (2011) had proved that a total solar eclipse affects the decrease in the pH of sea water as the content of hydrogen ions (H + ) contained in seawater would increase; and Sarah, Rusli, Othman, and Saupi (2016) had conducted a study on the impact of the phenomenon of the full moon on the tides along Malaysian coasts. The question is, to what extent is the relationship between astronomical phenomena with the maritime activities of fishermen?…”
Section: Introductionmentioning
confidence: 99%
“…During the total solar eclipse, some physical phenomena can be observed [1][2][3][4]. Reference [1] reported that this phenomenon affected to the meteorological parameters, such as solar radiation, temperature, and humidity.…”
Section: Introductionmentioning
confidence: 99%